A theoretical framework for vulnerability of heatwave-related mortality - Jianxiong HU; Guanhao HE; Wenjun MA (环境与职业医学, 2022)
In the context of global warming, the frequency, intensity, and duration of heatwaves will further increase. In recent years, plenty of studies have suggested from diversiform perspectives that heatwaves may increase mortality risk. However, the focuses of current studies on heat wave and human health are scattered, and a systematic theoretical framework has not yet been formed. We therefore systematically reviewed the previous literature in terms of possible mechanism paths and vulnerability mechanism of heatwave increasing mortality risk, summarized the vulnerability factors that influence exposure opportunities, constrain adaptive capacity, as well as affect physiological responses and behaviors. We further attempted to propose a theoretical framework from the processes of "exposure degree-modification effect-physiological behavior-health outcome". This paper summarized the research directions on heatwaves and health, which can provide ideas for future in-depth health risk assessment and adaptation to climate change.